2003
DOI: 10.1038/oby.2003.98
|View full text |Cite
|
Sign up to set email alerts
|

Sex Hormones and Sexual Function in Obese Men Losing Weight

Abstract: KAUKUA, JARMO, TUULA PEKKARINEN, TIMO SANE, AND PERTTI MUSTAJOKI. Sex hormones and sexual function in obese men losing weight. Obes Res. 2003;11:689-694. Objective: To study the impact of a weight-loss program on sex hormones and sexual function among 38 middle-aged obese men (BMI Ն35 kg/m 2 ). Research Methods and Procedures: A randomized controlled clinical trial was conducted. The treatment group (n ϭ 19) participated in a 4-month weight-loss program including 10 weeks on a very-low-energy diet (VLED) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
136
2
8

Year Published

2004
2004
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 195 publications
(158 citation statements)
references
References 17 publications
(27 reference statements)
12
136
2
8
Order By: Relevance
“…5 Weight loss was associated with a decrease in fasting insulin levels, increased mean plasma SHBG and total testosterone levels in both diabetic and nondiabetic intervention subjects, and free testosterone only in the diabetic men. This finding is concordant with that of other studies, which demonstrated improvements in total, 29 bioavailable 16 and free 29 testosterone levels after caloric restriction. For example, in a mixed group of diabetic and nondiabetic obese men, SHBG, total and free testosterone levels increased in response to a mean weight loss of 21 kg after 10 weeks of LCD.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…5 Weight loss was associated with a decrease in fasting insulin levels, increased mean plasma SHBG and total testosterone levels in both diabetic and nondiabetic intervention subjects, and free testosterone only in the diabetic men. This finding is concordant with that of other studies, which demonstrated improvements in total, 29 bioavailable 16 and free 29 testosterone levels after caloric restriction. For example, in a mixed group of diabetic and nondiabetic obese men, SHBG, total and free testosterone levels increased in response to a mean weight loss of 21 kg after 10 weeks of LCD.…”
Section: Discussionsupporting
confidence: 83%
“…27 In contrast to these data, an LCDinduced decrease in mean body mass index from 39.3 to 33.8 kg m À2 over 10 weeks failed to improve erectile function or sexual desire in middle-aged men with no history of ED. 16 Our study also showed strong associations between the increases in IIEF-5 and SDI scores with each other, and with the magnitude of reduction in weight and WC. Abdominal obesity is a marker of insulin resistance, and has strong epidemiological links with ED.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…For example, weight loss has been shown to improve testosterone levels, reducing fat mass and estrogen levels [135,136]. Modification may apply to changing prescription or nonprescription drug use and/or altering psychosocial factors [4].…”
Section: Step Care 3: Modifying Reversible Causesmentioning
confidence: 99%